2016
DOI: 10.5830/cvja-2016-039
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of FTY720 on functional recovery and infarct size following myocardial ischaemia/ reperfusion

Abstract: SummaryAimThe aim of this study was to evaluate the effects of the sphingosine analogue, FTY720 (Fingolimod), on the outcomes of myocardial ischaemia/reperfusion (I/R) injury.MethodsTwo concentrations of FTY720 (1 or 2.5 μM) were administered either prior to (PreFTY), or following (PostFTY) 20 minutes’ global (GI) or 35 minutes’ regional ischaemia (RI) in the isolated, perfused, working rat heart. Functional recovery during reperfusion was assessed following both models of ischaemia, while infarct size (IFS) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…FTY720 is a lipophilic immunomodulatory sphingosine-1-phosphate (S1P) analog, which is now used for treatment of multiple sclerosis and prevents T-lymphocyte egress from lymphoid organs ( 244 ). FTY720 reduces R/I to the other organs such as kidney, liver, and heart in the laboratory ( 221 , 222 ). Studies in cerebral ischemia have similarly shown reduction in I/R injury and improvement in neurological function ( 223 ).…”
Section: Anti-inflammatory Treatmentsmentioning
confidence: 99%
“…FTY720 is a lipophilic immunomodulatory sphingosine-1-phosphate (S1P) analog, which is now used for treatment of multiple sclerosis and prevents T-lymphocyte egress from lymphoid organs ( 244 ). FTY720 reduces R/I to the other organs such as kidney, liver, and heart in the laboratory ( 221 , 222 ). Studies in cerebral ischemia have similarly shown reduction in I/R injury and improvement in neurological function ( 223 ).…”
Section: Anti-inflammatory Treatmentsmentioning
confidence: 99%
“…The effect of FTY720 includes the induction of systemic lymphopenia, inhibition of inflammatory responses, and downregulation of intravascular adhesion molecules. Recently, several studies have shown that FTY720 protects organs from I/R injury, such as the liver [8,9], kidney [10,11], heart [12][13][14], and brain [15][16][17][18][19]. However, the mechanisms underlying the BBBprotective effects of FTY720 and time course of inflammatory modulation have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Egom et al, ). In a study by van Vuuren, Marais, Genade, and Lochner (), the effect of FTY720 on I/R injury has been investigated, and their results have demonstrated that FTY720 shows divergent effects in a dose‐dependent manner and time of administration. Another notable point is that high morbidity and mortality in cardiac transplant patients is related to I/R injury (Murata et al, ; Tanaka et al, ).…”
Section: Role Of S1p In Ischemia/reperfusion Injurymentioning
confidence: 99%